2004
DOI: 10.1136/inpract.26.4.182
|View full text |Cite
|
Sign up to set email alerts
|

Differential diagnosis of oral lesions and FMD in sheep

Abstract: THE clinical examination of sheep was among the many practical problems encountered during the 2001 pan-Asiatic type O foot-and-mouth disease (FMD) outbreak in the UK and was a cause for concern for many veterinary surgeons. The difficulty in diagnosing FMD arises from the fact that, often, only mild disease is seen in sheep and also because lesions associated with some of the common endemic diseases of sheep, such as interdigital dermatitis and orf (parapoxvirus infection), are similar in appearance. Oral les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 3 publications
1
14
0
1
Order By: Relevance
“…Clinical signs (acute fever, anorexia, vesicular lesions in the mouth and feet of infected animals with consequent excessive salivation, lameness and reduced productivity) determined in this study were in agreement with those reported for FMD [6,[11][12][13] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Clinical signs (acute fever, anorexia, vesicular lesions in the mouth and feet of infected animals with consequent excessive salivation, lameness and reduced productivity) determined in this study were in agreement with those reported for FMD [6,[11][12][13] .…”
Section: Discussionsupporting
confidence: 90%
“…However, even in some breeds of cattle, FMD can also be clinically difficult to recognize because of the mild appearance of the disease [10] . The disease is typically characterized by acute fever and the development of vesicular lesions in the mouth and feet of infected cloven-hoofed animals (principally cattle, pigs, sheep and goats) with consequent excessive salivation, anorexia, lameness, mortality of young animals and reduced productivity [10][11][12][13] . Foot-and-mouth disease usually has a high morbidity and low mortality, with mortality occurring mostly in young animals [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Other diseases causing postular lesions in the face are: pox, foot and mouth disease, blue-tongue disease, peste-des-petits-ruminants, sarcoptic mange, chorioptic mange and staphylococcal dermatitis (Wilson et al, 2002;Watson, 2004). Due to the nature of some of these diseases, it is important that the final diagnosis is achieved with high accuracy.…”
Section: Diagnosismentioning
confidence: 99%
“…Idiopathische, in der Mundhöhlenschleimhaut von kleinen Wiederkäuern, insbesondere am harten Gaumen und der Gingiva lokalisierte Ulzera werden seit der MKS-Epidemie 2001 im Vereinigten Königreich auch als OMAGOD ("ovine mucosal and gum obscure disease") bezeichnet. Offenbar sind diese Veränderungen bei Schafen recht weit verbreitet, waren aber vor näherer Inspektion während des Seuchengeschehens weitgehend unbemerkt geblieben (6,42). Die am häufigsten beobachteten Läsionen stellen sich als scharf begrenzte, meist schon in Abheilung befindliche Geschwüre in der bukkalen oder inneren Lippenschleimhaut unterhalb der Schneidezahnreihe dar.…”
Section: Pathogenese Und Pathologieunclassified